The Quality of Coconut Cream Torn Bread A Research Approach Based on Consumer Response - Rahmawati, Fani; Nugroho, Setyo Prasiyono; Sinangjoyo, Nikasius Jonet (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Ampat Yogyakarta, 2022)
This study aims to determine the quality of coconut milk as a substitute for liquid milk in the manufacture of torn bread in terms of quality, namely from the indicators of Appearance, Taste, Color, Aroma, and Texture. The sample of this study were residents of RT 07, located in the walnut alley Nologaten street, and several experts with a total of 30 panellists. The analysis used in this research is descriptive statistics. The variables measured were Appearance, Taste, Color, Aroma, and Texture. This study analyzes the data by conducting experiments and comparing the conclusions drawn based on consumer answers from expert interviews. In addition, the discussion of food quality, which consists of appearance, taste, colour, taste, and texture, is an inseparable unit, meaning that food quality is the basis of consumer response. The results show that in coconut milk, in making torn bread, it was proven that the taste, aroma, colour, texture and appearance factors got a